2007
DOI: 10.1016/j.exer.2006.10.003
|View full text |Cite
|
Sign up to set email alerts
|

Edinger-Westphal and pharmacologically stimulated accommodative refractive changes and lens and ciliary process movements in rhesus monkeys

Abstract: During accommodation, the refractive changes occur when the ciliary muscle contracts, releasing resting zonular tension and allowing the lens capsule to mold the lens into an accommodated form. This results in centripetal movement of the ciliary processes and lens edge. The goal of this study was to understand the relationship between accommodative refractive changes, ciliary process movements and lens edge movements during Edinger-Westphal (EW) and pharmacologically stimulated accommodation in adolescent rhes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
17
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3
1

Relationship

3
6

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 34 publications
(58 reference statements)
3
17
0
Order By: Relevance
“…Also, anatomical investigations in primates have revealed much about the sources of afferents to the EWpg that mediate accommodation. A number of studies have shown that electrical microstimulation in or immediately adjacent to the EW evokes ocular accommodation in primates (24, 61, 68, 118, 166, 173, 279, 280, 410, 418);. These results of EW stimulation are also consistent with studies in which electrical stimulation of the ciliary ganglion or nerves produced similar increases in accommodation in cats (232, 308).…”
Section: Autonomic Control Of Ocular Accommodationsupporting
confidence: 69%
“…Also, anatomical investigations in primates have revealed much about the sources of afferents to the EWpg that mediate accommodation. A number of studies have shown that electrical microstimulation in or immediately adjacent to the EW evokes ocular accommodation in primates (24, 61, 68, 118, 166, 173, 279, 280, 410, 418);. These results of EW stimulation are also consistent with studies in which electrical stimulation of the ciliary ganglion or nerves produced similar increases in accommodation in cats (232, 308).…”
Section: Autonomic Control Of Ocular Accommodationsupporting
confidence: 69%
“…[9][10][11][12][13][14] Edinger-Westphal and pharmacologically stimulated accommodation in rhesus monkeys demonstrate that the lens is the limiting factor in the accommodative response and that the ciliary muscle retains its ability to contract well beyond the onset of presbyopia. [9][10][11][15][16][17] Only within the last decade have improvements in noninvasive imaging technology allowed for similar studies in humans. To date, no study has undertaken a per diopter analysis of anatomical changes in both the crystalline lens and ciliary muscle in a single cohort of human subjects.…”
Section: Discussionmentioning
confidence: 99%
“…The study of aspects of accommodation and presbyopia in rhesus monkeys relies on the ability to induce accommodation. While this can be accomplished behaviorally in awake monkeys (Bossong et al, 2009), the ability to scrutinize and image different aspects of the accommodative movements in the eyes often relies on contact imaging techniques such as ultrasound biomicroscopy (Croft et al, 2009) and gonioscopy (Ostrin and Glasser, 2007; Rosales et al, 2008; Wendt et al, 2008) that require working on anesthetized monkeys. It is therefore necessary to be able to induce accommodation in anesthetized monkeys in a reliable and reproducible manner.…”
Section: Introductionmentioning
confidence: 99%